Novel Management for Severe Odontogenic Maxillary Sinusitis Based on Pathophysiology - Yoshio Ohyama; Masaru Ogawa; Satoshi Yokoo (Case Reports in Dentistry)
Endoscopic sinus surgery is commonly performed to treat odontogenic maxillary sinusitis. However, recurrence and natural ostium reclosure often occur due to the inadequate patency of the excretory route. Furthermore, classical maxillary sinus radical surgery is still performed for odontogenic maxillary sinusitis even though it can cause postoperative maxillary sinus deformation, loss of function, and a postoperative maxillary cyst. A management that addresses these issues has not yet been identified. This study reported a conservative maxillary sinus management, wherein a nasoantral window is prepared and the thickened maxillary sinus mucosa is preserved, using the Caldwell–Luc approach. This study presents a case of severe odontogenic maxillary sinusitis that spread to the frontal sinus. This novel management facilitated complete recovery from severe odontogenic maxillary sinusitis in this case.